2011
DOI: 10.2478/s11536-011-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model of repeat induced abortion in Hungary

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
3
3
1
Order By: Relevance
“…Besides, with respect to the participants themselves, their age, education, occupation, parity, and cognition of the possible adverse health effects of having an abortion were significantly associated with the repeat abortion. First, in line with prior studies [ 4 7 , 10 13 , 19 , 23 26 , 28 , 41 , 44 , 49 , 52 ], we found that an increased age of women was strongly associated with a higher risk of having repeat abortions. This association is not surprising and reflects the longer exposure to sexual intercourse and thereby increased risks of unintended pregnancies for these older women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, with respect to the participants themselves, their age, education, occupation, parity, and cognition of the possible adverse health effects of having an abortion were significantly associated with the repeat abortion. First, in line with prior studies [ 4 7 , 10 13 , 19 , 23 26 , 28 , 41 , 44 , 49 , 52 ], we found that an increased age of women was strongly associated with a higher risk of having repeat abortions. This association is not surprising and reflects the longer exposure to sexual intercourse and thereby increased risks of unintended pregnancies for these older women.…”
Section: Discussionsupporting
confidence: 91%
“…In the U.S., the percentage of repeat abortion among women undergoing an abortion ranged from 44.8 to 58.8% [ 4 7 ]. Other studies conducted in the U.K., Switzerland, Norway, Italy, Netherlands, Finland, Ethiopia, Georgia, Ghana, Kenya, Nigeria, Tunisia, Vietnam, Nepal, Hungary, Russia, and Canada reported that the prevalence of repeat abortion among women receiving an abortion or having had an abortion were 19.2–23.4% [ 8 , 9 ], 30.1% [ 10 ], 36.7% [ 11 ], 60.6% [ 12 ], 36.0% [ 13 ], 14.1–37.9% [ 14 , 15 ], 20.3–34.9% [ 16 18 ], 69.9% [ 19 ], 33.7% [ 20 ], 14.3% [ 21 ], 23.0% [ 22 ], 42.2% [ 23 ], 31.7% [ 24 ], 32.3% [ 25 ], 46.1% [ 26 ], 23.6% [ 27 ], and 31.8% [ 28 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Age, education, residence, and migration status were not significantly influencing factors related to repeat abortions of adolescents who were receiving abortions, which contradicted the results of prior studies on young women [ 15 , 27 , 30 , 34 , 42 , 45 , 47 , 48 , 49 , 50 , 51 , 55 , 56 , 57 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Parity was the fourth and a strong risk factor, which has been previously verified in the literature to have a positive effect on increasing the risk of repeat abortions in China and many other countries [2,5,30,45,47,48,49,50,51,52,53,54]. Women who had children were inclined to have repeat abortions compared with those without a child.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation